The world-wide invader Deltamysis holmquistae expanded to the East Atlantic and Diamysis lagunaris to the North Sea (Crustacea, Mysida) - Karl J. Wittmann; Ton van Haaren; Rianna Vlierboom (Aquatic Invasions)
In October 2023 and April 2024, ecological monitoring was undertaken in brackish waters of the North Sea Canal, a major shipping route linking the Port of Amsterdam to the North Sea. Amongst the macrobenthic samples, four endemic and three non-native mysid species were recorded, two of the latter for the first time in this locality. This concerns the now globally distributed Deltamysis holmquistae, and the Mediterranean Diamysis lagunaris. Based on the spatial context, these specimens are highly likely to have been introduced through human-mediated transport, with shipping providing the most obvious entry path into the North Sea Canal. Both species were found in fully artificial and in restored near-natural habitats, highlighting their versatility as invasive species. Pictorial descriptions and complete keys for both species are included in order to facilitate future assessments of potential range expansions.